Current definition, diagnosis, and treatment of canine and feline idiopathic vestibular syndrome - Mertens, Anna Morgana; Schenk, Henning Christian; Volk, Holger Andreas (Frontiers in Veterinary Science, 2023)
Idiopathic vestibular syndrome (IVS) is one of the most common neurological disorders in veterinary medicine. However, its diagnosis and treatment varies between publications. The aim of the current study was to gather experts' opinion about IVS definition, diagnosis, and treatment. The study demonstrated that the definition, diagnosis, and treatment of IVS are largely consistent worldwide, with the EU prioritising less frequently advanced imaging and more often otoscopy to rule out other diseases. IVS was defined by most specialists as an acute to peracute, improving, non-painful peripheral vestibular disorder that often affects cats of any age and geriatric dogs. Regarding diagnosis, a detailed neurological examination and comprehensive blood tests, including thyroid values, blood pressure, and otoscopic examination, was seen as crucial. A thorough workup may also involve MRI and CSF analysis to rule out other causes of vestibular dysfunction. Treatment of IVS typically involved intravenous fluid therapy and the use of an antiemetic, with maropitant once daily being the preferred choice among specialists. Antinausea treatment was considered, however, only by a handful specialists. This survey-based study provides valuable insights from neurology experts and highlights areas that require further research to bridge the gap between theory and practice.